Happy Dog, Happy You: Quick Tips for Building a Bond with Your Furry Friend - Arden Moore
Pet expert Arden Moore offers hundreds of games, reward-based training routines, and grooming tips that will keep your dog healthy, happy, and engaged. Filled with practical tips and techniques for strengthening the bond between you and your canine companion, this fun and informative guide will have you learning the secrets of doggie massage and jumping behind trees as you play hide-and-seek. Enjoy hours of dog-filled fun while inspiring your pet to be the best he can be.